An integrated microbiome- and metabolome-genome-wide association study reveals the role of heritable ruminal microbial carbohydrate metabolism in lactation performance in Holstein dairy cows - Chenguang Zhang; Huifeng Liu; Xingwei Jiang; Zhihong Zhang; Xinfeng Hou; Yue Wang; Dangdang Wang; Zongjun Li; Yangchun Cao; Shengru Wu; Sharon A. Huws; Junhu Yao (Microbiome)
Abstract Background Despite the growing number of studies investigating the connection between host genetics and the rumen microbiota, there remains a dearth of systematic research exploring the composition, function, and metabolic traits of highly heritable rumen microbiota influenced by host genetics. Furthermore, the impact of these highly heritable subsets on lactation performance in cows remains unknown. To address this gap, we collected and analyzed whole-genome resequencing data, rumen metagenomes, rumen metabolomes and short-chain fatty acids (SCFAs) content, and lactation performance phenotypes from a cohort of 304 dairy cows. Results The results indicated that the proportions of highly heritable subsets (h 2  ≥ 0.2) of the rumen microbial composition (55%), function (39% KEGG and 28% CAZy), and metabolites (18%) decreased sequentially. Moreover, the highly heritable microbes can increase energy-corrected milk (ECM) production by reducing the rumen acetate/propionate ratio, according to the structural equation model (SEM) analysis (CFI = 0.898). Furthermore, the highly heritable enzymes involved in the SCFA synthesis metabolic pathway can promote the synthesis of propionate and inhibit the acetate synthesis. Next, the same significant SNP variants were used to integrate information from genome-wide association studies (GWASs), microbiome-GWASs, metabolome-GWASs, and microbiome-wide association studies (mWASs). The identified single nucleotide polymorphisms (SNPs) of rs43470227 and rs43472732 on SLC30A9 (Zn2+ transport) (P < 0.05/nSNPs) can affect the abundance of rumen microbes such as Prevotella_sp., Prevotella_sp._E15-22, Prevotella_sp._E13-27, which have the oligosaccharide-degradation enzymes genes, including the GH10, GH13, GH43, GH95, and GH115 families. The identified SNPs of chr25:11,177 on 5s_rRNA (small ribosomal RNA) (P < 0.05/nSNPs) were linked to ECM, the abundance alteration of Pseudobutyrivibrio_sp. (a genus that was also showed to be linked to the ECM production via the mWASs analysis), GH24 (lysozyme), and 9,10,13-TriHOME (linoleic acid metabolism). Moreover, ECM, and the abundances of Pseudobutyrivibrio sp., GH24, and 9,10,13-TRIHOME were significantly greater in the GG genotype than in the AG genotype at chr25:11,177 (P < 0.05). By further the SEM analysis, GH24 was positively correlated with Pseudobutyrivibrio sp., which was positively correlated with 9,10,13-triHOME and subsequently positively correlated with ECM (CFI = 0.942). Conclusion Our comprehensive study revealed the distinct heritability patterns of rumen microbial composition, function, and metabolism. Additionally, we shed light on the influence of host SNP variants on the rumen microbes with carbohydrate metabolism and their subsequent effects on lactation performance. Collectively, these findings offer compelling evidence for the host-microbe interactions, wherein cows actively modulate their rumen microbiota through SNP variants to regulate their own lactation performance. Video Abstract